2022
DOI: 10.1055/s-0042-1756215
|View full text |Cite
|
Sign up to set email alerts
|

Correlação entre posicionamento do cage e lordose lombar em fusão transforaminal minimamente invasiva (TLIF)

Abstract: Resumo Objetivo Avaliar os resultados radiográficos e comparar a lordose pós-operatória em técnica de artrodese intersomática lombar transforaminal (TLIF, na sigla em inglês), considerando como variável o posicionamento do dispositivo intersomático (cage) em relação ao espaço discal. Métodos Análise retrospectiva radiográfica de pacientes cirúrgicos, em nível único, por doença lombar degenerativa, aplicando-se TLIF e instrumentação pedicular posterior. Os pacientes foram divididos, conforme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Several authors have found that anterior fusion techniques portend an increased sagittal correction, focusing on improving segmental lordosis (SL), disc height (DH), and lumbar lordosis (LL) 7–9,11,12 . Interestingly, TLIF cage placement, but not cage lordosis or footprint, has been shown to impact sagittal balance parameters, namely SL and DH 13–17 . The increased lordosis observed in anteriorly placed TLIF cages may allow a more accurate comparison of TLIF and ALIF procedures; however, no investigation has directly compared ALIFs to TLIFs with an anteriorly placed cage.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have found that anterior fusion techniques portend an increased sagittal correction, focusing on improving segmental lordosis (SL), disc height (DH), and lumbar lordosis (LL) 7–9,11,12 . Interestingly, TLIF cage placement, but not cage lordosis or footprint, has been shown to impact sagittal balance parameters, namely SL and DH 13–17 . The increased lordosis observed in anteriorly placed TLIF cages may allow a more accurate comparison of TLIF and ALIF procedures; however, no investigation has directly compared ALIFs to TLIFs with an anteriorly placed cage.…”
mentioning
confidence: 99%
“…[7][8][9]11,12 Interestingly, TLIF cage placement, but not cage lordosis or footprint, has been shown to impact sagittal balance parameters, namely SL and DH. [13][14][15][16][17] The increased lordosis observed in anteriorly placed TLIF cages may allow a more accurate comparison of TLIF and ALIF procedures; however, no investigation has directly compared ALIFs to TLIFs with an anteriorly placed cage.…”
mentioning
confidence: 99%